Wicked ID: Conceptual Framework for Considering Instructional Design as a Wicked Problem - Katrin Becker (The Canadian Network for Innovation in Education (CNIE), 2007)
The process of instructional design has parallels in other design disciplines. Software design is one that has experienced intense attention in the last 30 or so years, and many lessons learned there can be applied to ID. Using software design as a springboard, this concept paper seeks to propose a new approach to ID. It suggests that instructional design is almost always a Wicked Problem. The connection is formed between Wicked Problems as first described by Rittel and Webber in 1973, and the models in and processes of instructional design. The areas of social planning, organizational management and software design all posses some accepted and tested approaches to the solution of Wicked Problems. These will be described, and how they can be applied to ID will be explained. Finally, this paper will propose a meta-model for ID and explain how it can be used in the current context. Résumé : Le processus de conception pédagogique a des similitudes avec d'autres disciplines. La conception de logiciels a fait l'objet d'une grande attention dans les trente dernières années et de nombreuses leçons tirées peuvent s'appliquer à la conception pédagogique. En se basant sur la conception de logiciels, cet article cherche à proposer une nouvelle méthode à la conception pédagogique. Il laisse entendre que la conception pédagogique constitue presque toujours un problème épineux. Le lien est formé entre les problèmes épineux tels que décrits par Rittel et Webber en 1973 et les modèles et processus de la conception pédagogique. Les secteurs de l'organisation sociale, de la gestion des organisations et de la conception de logiciels comptent des méthodes acceptées et validées à la résolution de problèmes épineux. Nous les décrirons et expliquerons comment ils peuvent servir à la conception pédagogique. Enfin, l'article proposera un meta-modèle de la conception pédagogique et expliquera comment il peut servir dans le contexte actuel.